Sündmus, kogemus ja jutustamine - Kirsti Salmi-Niklander (Mäetagused, 2009)
The article analyzes the interdependency of event, experience, and narrating. What does the event consist of in academic historical research and in oral history? How do narrators define events in everyday life, when reminiscing and narrating? The article discusses the event as the common area of history and anthropology. The aim of the article is to search for new information on historical processes that are observed through the experience of contemporaries of such events by analysing the interdependency of the event and the experience, and how they are expressed. A precise analysis of twoevent narratives that remain in the borderland of oral and written expression is used to disclose the processes of social breakthrough in the 1890s: women entering the previously male-dominated areas of life and the resulting power struggle, the activities of temperance societies in changing student life, the development of new communitiesand new means of expression. The narrative styles and genre transformation were caused by the fact that the existing means of expression were inadequate for recording the changes that occurred and were perceived in the society.